A first course in software engineering methods and theory (2014)
Even though the software engineering curriculum has been designed many times, some problems still remain: the gap between academy and industry, the failure to continuously update the courses, the difficulties for combining theory and practice, and the lack of a sound, widely accepted theoretical basis. The SEMAT (Software Engineering Methods and Theory) initiative has been proposed for addressing some of the aforementioned problems. Based on the main ideas related to SEMAT, in this paper we propose a first course that introduces students to the main issues about SEMAT. This course is planned to be included in the System and Informatics Engineering Program belonging to the Universidad Nacional de Colombia, Medellin Branch. Also, we discuss the way in which this course addresses the previously diagnosed problems.